Structural determination of amyloid firils by electron spin resonance - Pornsuwan, Soraya (Asia-Pacific Journal of Science and Technology, 2017)
Aggregation of some proteinsand peptides intoamyloid firils is directly related to many protein-misfoldingdiseases including those from neurodegeneration suchas Alzeimer’s and Parkinson’s diseases. Determination ofthe firil structure and the firillation process is essential for developing methods to control the aggregation process.However, presenttechniques developed for analysis of the aggregationprocess have been challenged due to the lack of well-defied and complicated structures in the firillarstage. This review describes the principleand application ofnitroxide spin-labeling strategy combined with Electron Spin Resonance (ESR) as an alternative tool for monitoring the firil process. The progress ofthe technique for revealing insights in the molecular level isdiscussed. Finally, the future direction of the ESR application for providinganalysis of structural detail and drug design for preventing amyloidfiril formation is commented.